Reforma Al Código Orgánico Integral Penal Tipificando como delito autónomo las lesiones que producen incapacidad reproductiva de la víctima - Torres Castillo, Jonathan Ramiro (2022)
The present thesis is entitled: "REFORM TO THE INTEGRAL CRIMINAL ORGANIC CODE TYPIFYING AS AN AUTONOMOUS CRIME THE INJURIES THAT PRODUCE REPRODUCTIVE INABILITY OF THE VICTIM", and its interest to develop is due to the legal vacuum that exists in the Integral Organic Penal Code by not distinguishing the injuries that cause reproductive incapacity in the victim, since these injuries are alien to what is expressed in article 152 of the Integral Organic Penal Code , Thanks to the contribution of several legal specialists it has been possible to demonstrate that by not integrating the crime of injuries that cause reproductive incapacity in the Ecuadorian criminal law, constitutional rights such as the right to health are violated, since these practices of genital mutilation are carried out with malice and for non-medical purposes. The first civilizations such as Egypt, Babylon, Greece, Israel, Rome were references of how Criminal Law was applied where custom and revenge was the primitive form of punishing crimes. In this thesis, materials and methods were applied that allowed the development of the research, as well as ten interviews and thirty surveys to criminal law professionals and specialists in forensic medicine, results that served to propose the legal reform project to the Organic Integral Penal Code to include the crime of injury that prevent reproduction in the catalog of crimes and to guarantee the right to health.